Evaluation of Cortez Onestep Chlamydia RapicardTM Insta Test for the Detection of Chlamydia Trachomatis in Pregnant Women at Mbare Polyclinic in Harare, Zimbabwe - Stephen Stephen, MSc; Chiwoneso Gwyneth Elizabeth Muchaneta-Kubara, PhD; Marshall Wesley Munjoma, PhD; Gibson Mandozana, PhD (Global Health and Education Projects, Inc., 2016)
Background: Cervical chlamydia infection poses high risk of pregnancy complications and neonatal infection. Reference methods for the detection of chlamydia infection are not available for routine use in developing countries. Point-of-care (POC) tests can bridge this gap. This study evaluated Cortez Onestep Chlamydia RapicardTM insta test for the detection of Chlamydia trachomatis in pregnant women at Mbare Polyclinic and determined the prevalence of C. trachomatis. Methods: This was a cross sectional study in 242 pregnant women aged ≥18 years attending their first ANC visit at Mbare polyclinic in Harare, Zimbabwe. Data collection form was used to obtain demographic and predisposing factors to Chlamydia infection and two endocervical swabs were collected from each patient. One specimen was examined by the POC test at the clinic and the other by SDA method in the laboratory. Results: The sensitivity, specificity, positive and negative predictive values of the rapid kit were 71.4%, 99.6%, 90.9% and 98.3% respectively. Prevalence of C. trachomitis was 5.8% by SDA method. Conclusion and Global Health Implications: The kit's sensitivity (71.4%) and specificity (99.6%) implies that the rapid test is an important test which needs further evaluations. The prevalence of C. trichomitis of 5.8% is comparable to studies done elsewhere in Africa. Key words: Chlamydia trachomatis • Antenatal Clinic • Point of Care Tests • Rapid Test • Cortez One Step Chlamydia Test Copyright © 2017 Stephen et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.